LEMBAGA KERJASAMA (LKS) BIPARTIT PERUSAHAAN DALAM PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL DI KABUPATEN DELI SERDANG - Rika Jamin Marbun; Budiman Ginting; Pendastaren Tarigan; Agusmidah Agusmidah (Universitas Sumatera Utara, 2017)
abstract Employer, employee/labor and government always take efforts to build an harmonious industrial relationship in any companies in order to achieve the high productivity and labor prosperous. The harmonious industrial relationship will minimize any conflict in industrial relationship such as the employer and employee. One of efforts to prevent the dispute in industrial relationship between employer and employee is by establishment of forum of communication, consultation and mutual deliberation between the employer and representative of labor union in the company level as determined in the Act No. 13 of 2003 concerning to the labor affairs on article 106 that known as Bi party Mutual Cooperation Agent. The problem would analyzed in this thesis is how the existence of bi party mutual cooperation agency in regency of Deli Serdang, what the role and its function in the settlement of the dispute of industrial relationship and what the sanction and the implementation of the sanction to the company that did not establish the bi party mutual cooperation agent. The applied method in this research is analytic descriptive with judicial normative study. The data from Labor and Transmigration office of Deli Serdang Regency in 2012 indicates that the number of dispute cases in industrial relationship were 84 cases and can be settled by bi party for 47.61%. in 2013, the number of case were 108 case and can be settled for 50.92%. in 2014, the number of industrial relation disputes were 134 cases and can be settled for 58.9%. Based on the number of cases as shown by the data of Labor and Transmigration office of Deli Serdang Regency, bi party mutual cooperation agent (LKS) is required to prevent the dispute in industrial relation. The existence of this agent in the company will minimize the dispute in industrial relation between employer and employee if there is any dispute in industrial relationship that can be settled by by party. The government, the minister of labor affairs is hope to issue the implementation rule of the administrative sanction so the labor and transmigration office will punish the company that have not bi party mutual cooperation agency (LKS). Keywords : Bi party Mutual Cooperation Agent and Industrial Relationship Dispute.